(untitled) (Plant Tissue Culture and Biotechnology, 2016)
The effect of glutamine, biotin and adenosine diphosphate (ADP) on growth and cultivars micropropagation of three ornamental species was investigated. The addition of 10 ? 100 mg/l glutamine in culture media significantly increased rate of multiplication in Cordyline fruticosa and 100 mg/l glutamine showed the same effect for Gerbera jamesonii. Addition of glutamine did not show any effect on shoot length, root number and length in all the three species. Addition of 1 ? 3 mg/l biotin increased shoot length of Gerbera jamesonii but inhibited shoot length of Cordyline fruticosa and decreased root length of Chrysanthemum hybridum and Gerbera jamesonii. Addition of 5.0 mg/l ADP significantly increased multiplication rate of Cordyline fruticosa and 1.0 mg/l ADP showed similar effect for Gerbera jamesonii. Plant Tissue Cult. & Biotech. 26(1): 97-104, 2016 (June)